The Ash Discharged by Sheveluch Volcano (Kamchatka, Russia) in April 2023 As a Source of Water-Soluble Salts - Sergeeva A.V.; Girina O.A.; Nazarova M.A.; Kartasheva E.V.; Pozolotina L.A.; Kuzmina A.A.; Plutakhina E.Yu. (Journal of Volcanology and Seismology, 2024)
This paper considers the propagation of ash during the paroxysmal eruption of Sheveluch Volcano which occurred April 10–13, 2023, and its impact on the water resources of the affected area. We characterize ash thicknesses at various population centers and describe the grain-size composition of the ash. We show that the propagation of ash plumes is primarily driven by the eruption dynamics, but atmospheric circulation actually controls the spatial distribution of deposit thickness. The water-soluble salts contained in the ash and the dynamics of their washing out under natural conditions have been determined. The water-soluble part of fresh ash is dominated by calcium and magnesium sulfates, sodium chloride, with minor amounts of chlorides and fluorides of aluminum, potassium, and ammonium. The first substances to be washed out from ashes are well-soluble chlorides, to be followed by sulfates. As time goes on, the total concentration of soluble salts is decreasing, and their qualitative composition changes: hydrogen carbonates of calcium, magnesium, and sodium begin to dominate. Several months after the eruption, the impact of the ashfall on water resources of the settlements, including open springs at the ground surface, was leveled out.